59.6k views
0 votes
Which expression is equivalent to (2mn)^4/6m^-3n^-2? assume m and n cannot equal 0

User VyvIT
by
4.3k points

2 Answers

2 votes

Answer:

the asnwer is A

Explanation:

3 votes

Answer:

=8/3m⁷n⁶

Explanation:

Given the expression (2mn)⁴/6m⁻³n⁻², we first solve the numerator

(2mn)⁴ = 16m⁴n⁴

The new expression becomes 16m⁴n⁴/6m⁻³n⁻²

We now divide the coefficients and the exponents as follows:

=16/6ₓ(m⁴/m⁻³)×(n⁴/n⁻²)

Division between indices to the same base we subtract the powers.

4-⁻3=7

4-⁻2=6

=8/3m⁷n⁶

User Teenup
by
4.3k points